Studies in Christian ethics ; vol. 3 no 1 - Franklin, Richard (Edinburgh, Scotland T and T Clark, 1991)
Contents : v. 3:1 : Political ethics. Includes bibliographical references.
Keywords: Political ethics -- religious aspects -- Christianity